PERANCANGAN MASKOT PRODUK BOWAH (BOBA BUWAH NAGA) - Raia, Divanna Hikary (Jurnal Industri Kreatif dan Inovatif, 2024)
In the business world, branding and brand identity are important keys to creating a positive impression on consumers and increasing the competitiveness of local products in the global market. This journal discusses the process of designing the mascot "Boba Buwah Naga (Bowah)" - a beverage product developed by Institute students Bukit Harapan Christian Technology and Business. By referring to the method developed by Aline Wheeler, the Bowah mascot design process includes five stages, namely research, clarifying the strategy, designing the identity, creating touch points, and managing assets. The Bowah mascot is an imaginative work that represents the product uniquely and is easily recognized by consumers. It is hoped that the Bowah mascot design will make a deep impression on the audience and become a strong foundation for Bowah's branding in the future. Apart from that, this journal is also expected to become a reference and source of inspiration for business people who are interested in brand development and product branding, especially for local Indonesian products who want to increase their competitiveness in the global market.